Туристично-країнознавчі особливості розвитку туризму в Литві - Мандрик, Ірина; Савчук, Вікторія; Mandryk, Irina; Savchuk, Viktoriya (My University, 2017)
Розглянуто особливості та тенденції розвитку туризму в Литві з позицій туристичного країнознавства. Показано місце й роль туризму в економіці цієї держави. Проаналізовано динаміку та географічну структуру туристичних потоків. Названо основні країни-постачальники іноземних туристів до Литви. Виявлено, що в останні роки значно зменшився притік туристів із Росії, натомість туристичний ринок Литви заміщується туристами з країн Європейського Союзу. Указано на те, що, крім іноземного туризму, у Литві вагому роль відіграє внутрішній туризм, який демонструє тенденцію до зростання. Охарактеризовано основні види туризму Литви та визначено найважливіші чинники, що сприяють їх розвитку. Названо й проаналізовано найважливіші туристичні центри країни (Вільнюс, Тракай, Каунас, Шяуляй, Клайпеда, Друскінінкай). Визначено основні проблеми й перспективні напрями розвитку туризму в Литві. The present article deals with the study of the tourism features development in Lithuania. The text gives a valuable information on features and trends of tourism development in Lithuania based on tourist-regional research. Special attention is given to the place and role of tourism in the Lithuanian economy. The article mentions dynamics and geographic structure of tourist flows. Named the main supplier countries of foreign tourists to Lithuania. It is specially noted that the inflow of tourists from Russia has diminished in recent years, whereas the tourism market in Lithuania has been replaced by tourists from the countries of the European Union. In addition to foreign tourism, the role of domestic one in Lithuania shows a tendency to increase. The text gives a valuable information on the main types of tourism in Lithuania and identifies the most important factors contributing on their development. A mention should be mad that the most important tourist centers of the country are Vilnius, Trakai, Kaunas, Šiauliai, Klaipeda, Druskininkai. The article describes problems and perspective directions of tourism development in Lithuania.
Tourist-country Studies Features of Tourism devElopment in Lithuania
Keywords: туризм; туристичне країнознавство; туристичний потік; види туризму; туристичний центр; Литва; tourism; tourist country-specific studies; tourist stream; types of tourism; tourist center; Lithuania